NALYSIS OF PERSONAL DATA PROTECTION OF TELECOMMUNICATIONS SERVICE USERS - Itok Dwi Kurniawan (SOSIOEDUKASI, 2024)
Technological developments in the digital era have implications for global information openness. We can easily find information from all parts of the world. Along with this development, there is a problem that is quite crucial, namely related to the protection of personal data of communication service users. The purpose of writing this article is to determine the legal protection for personal data of telecommunications service users. This article was written using normative legal research methods with a statutory approach. The results of this research show that personal data is part of the right to privacy which is included in human rights so its protection must be guaranteed by law. Misuse of personal data is a form of information technology crime that can be subject to criminal sanctions.